Industrial hygiene and safety implications of radiofrequency use in particle accelerator technologies - Vyom Saxena (Radiation Protection and Environment)
Despite their essential contributions, particle accelerators present unique occupational hazards, including exposure to ionizing radiation, high-voltage systems, cryogenic temperatures, and risks associated with handling hazardous materials and strong electromagnetic fields. Among these, radiofrequency (RF) exposures – primarily from RF cavities and auxiliary equipment – pose significant health and safety risks. Effective mitigation strategies are critical to safeguarding personnel. These strategies include adherence to established guidelines and standards, comprehensive risk assessments, and the implementation of engineering controls, administrative measures, and personal protective equipment. This article discusses the importance of these measures in reducing health risks related to accelerator operations, with a particular focus on RF exposures. Case studies on RF emission control and mitigation practices at select accelerators are presented to illustrate effective occupational safety strategies. The high-power RF systems at low-energy high-intensity proton accelerator and Electron Beam Center employ advanced shielding, RF monitoring, and safety interlocks to minimize RF radiation exposure, ensuring compliance with strict safety standards and enabling incident-free operation of particle accelerators.